Bioinformatics analyses and in vitro evidence for five and six stacked G-quadruplex forming sequences - Bartas, Martin; Brázda, Václav; Karlický, Václav; Červeň, Jiří; Pečinka, Petr (Biochimie, 2018)
Quadruplexes are noncanonical DNA structures that arise in guanine rich loci and have important biological functions. Classically, quadruplexes contain four stacked intramolecular G-tetrads. Surprisingly, although some algorithms allow searching for longer than 4G tracts for quadruplex formation, these have not yet been systematically studied. Therefore, we analyzed the human genome for sequences that are predicted to adopt stacked intramolecular G-tetrads with greater than four stacks. The data provide evidence for numerous G-quadruplexes that contain five or six stacked intramolecular G-tetrads. These sequences are predominantly found in known gene regulatory regions. Electrophoretic mobility assays and circular dichroism spectroscopy indicate that these sequences form quadruplex structures in vitro under physiological conditions. The localization and in vitro stability of these G-quadruplexes indicate their potentially important roles in gene regulation and their potential for therapeutic applications.
Keywords: Circular Dichroism; G-quadruplex; Electrophoresis; konformace nukleové kyseliny; G-kvadruplexy; Nucleic Acid Conformation; Circular dichroism; Bioinformatics; Computational Biology; G-Quadruplexes; cirkulární dichroismus; výpočetní biologie